Is exposure to tobacco associated with extrahepatic cholangiocarcinoma epidemics? A retrospective proportional mortality study in China - Lei Hou (BMC Cancer, 2019)
Abstract Background Extrahepatic cholangiocarcinoma (ECC) has become one of the most rapidly increasing malignancies in China during recent decades. The relationship between tobacco exposure and ECC epidemics is unclear; this study aimed to explore this relationship. Methods We included 55,806 participants aged 30 years or older from the National Mortality and Smoking Survey of China. Smoking in participants and spouses was defined as 1 cigarette or more per day for up to 1 year. Spouses’ smoking was taken as a measure of exposure to passive smoking. Smoking information in 1980 was ascertained and outcomes were defined as ECC mortality during 1986–1988. Results We found that either passive or active smoking increased the risk of death from ECC by 20% (risk ratio [RR], 1.20; 95% confidence interval [CI], 0.99–1.47), compared with no exposure to any tobacco. This risk was a notable 98% (RR, 1.98; 95% CI, 1.49–2.64) for individuals exposed to passive plus active smoking. These findings were highly consistent among men and women. Pathology-based analyses showed dose-response relationships of ECC with pack-years for all types of smoking exposure (Ps for trend < 0.05); the RR reached 2.75 (95% CI, 1.20–6.30) in individuals exposed to combined smoking with the highest exposure dose. The findings were similar for non-pathology-based analysis. Conclusions This study indicates that tobacco exposure increases ECC risk. Given the dramatic increase of exposure to secondhand smoke and patients with ECC, an inadequate provision of smoke-free environments could be contributing to ECC epidemics and could further challenge public health and medical services, based on the current disease spectrum.